Selected challenges in solidification processing of graphene nanoplatelets (GNPs) reinforced aluminum alloys composites - Ghaderi, Omid; Zare, Mehran; Niroumand, Behzad; Church, Benjamin C.; Rohatgi, Pradeep K. (Frontiers in Materials, 2024)
Solidification processing of aluminum graphene composite is an attractive option for synthesis of metal matrix composites. Graphene reinforced aluminum metal matrix composites (GAMMCs) are of interest due to the low density and ultrahigh physical and mechanical properties of Graphene which can improve the properties of Al-Graphene composites. However, solidification processing of aluminum graphene composites has served challenges, including agglomeration of reinforcement and porosity resulting in decrease in properties above 0.5-3 wt% graphene. Also, the graphene surface can react with molten aluminum alloys to form aluminum carbide. Challenges with particle distribution and porosity are frequently caused by the poor wetting of reinforcement by melt, requiring additions of selected wetting agents. The other problems include movement of reinforcement within the melt due to density differences and convection leading to nonuniform distribution of reinforcements. The graphene reinforcements can be pushed by solidifying interfaces under certain conditions during solidification leading to segregation of reinforcements in the interdendritic regions. The paper critically analyzes the above problems related to solidification processing of Aluminum-Graphene composites which has not been done in previous publications aluminum-graphene composites. The objective of this paper is to examine the challenges, and suggest possible solutions including addition of elements like silicon and magnesium to aluminum melt, coating graphene with metals like nickel and copper, controlling rate of advancement and nature of advancing solid liquid interface in a manner that they engulf graphene with dendrites or grains.